THE DEVELOPMENT OF ADMINISTRATIVE COMPETENCY MODEL TO SERVE THE BEST PRACTICE ORGANIZATION OF MUNICIPALITIES IN THE NORTHEASTERN REGION, THAILAND - Thananant, Prasit; Maythaisong, Suthep; Phansawang, Jiraporn (Journal of Social Science and Cultural, 2023)
This research article aims to 1) study the administrative competency, 2) select the administrative competency, and 3) to create a model and guidelines for enhancing the administrative competency to serve the best practice organization as mentioned. This research is mixed-method research. The sample group was 502 municipal officials working in the Northeastern region. The research tools were questionnaires, interview forms, model assessment forms, and guidelines for building high-performance organizations. The statistics used in the research were percentage, mean, standard deviation. Confirmatory component analysis and tests for normal and ladder multiple regression analysis. The research findings were as follows: 1) The administrative competency factors and indicators for prediction to serve the best practice organization of Municipalities in The Northeastern Region, Thailand consist of seven factors: 1.1) Human resource management. 1.2) Network management. 1.3) Organization-wide quality management. 1.4) Performance-based management. 1.5) Social Capital Management. 1.6) Kaizen Management and 1.7) Horenzo Management. 2) The factors for selection of management administrative competency to serve the best practice organization of Municipalities could be categorized in four categories based on high to low values, namely, Kaizen management, performance-oriented management, organization-wide quality management and network management. 3) A model and approaches constructed for enhancing the administrative competency to serve the best practice organization cononsist of three parts: 3.1) Input factors consisting of Kaizen management, 3.2) Process factors consisting of PDCA model integrated with the four principles of Sangahavatthu in Buddhism and 3.3) Output factors, i.e. high performance organizations and the guidelines for enhancing the organization to produce high performances.